2003
DOI: 10.1029/2003jb002426
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the Trans‐European suture zone region along POLONAISE'97 seismic profile P4

Abstract: [1] The large-scale POLONAISE'97 seismic experiment investigated the velocity structure of the crust and upper mantle in the Trans-European suture zone (TESZ) region between the Precambrian east European craton (EEC) and Paleozoic platform that comprises terranes added during the Caledonian and Variscan orogenies respectively). This experiment included 64 shots recorded by 613 seismic stations during two deployments. Very good quality data were recorded along five profiles, and the longest and most important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 49 publications
12
141
0
5
Order By: Relevance
“…The edge of the EEC in the basement level is relatively clear and defines the southwestern range of the craton. However, another criterion in the continental scale could be one more-crustal criterion, e.g., range of the high velocity lower crust beneath EEC (Grad et al , 2003a(Grad et al , b, 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The edge of the EEC in the basement level is relatively clear and defines the southwestern range of the craton. However, another criterion in the continental scale could be one more-crustal criterion, e.g., range of the high velocity lower crust beneath EEC (Grad et al , 2003a(Grad et al , b, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Basement in the TESZ area is not reached by boreholes (see dashed pink lines at depth of 5 km), so its depth and velocity is available only from seismic profiles. FSB Fore-Sudetic Block, K-P Synclinorium Kościerzyna-Puławy Synclinorium, MPA Mid-Polish Anticlinorium, NSS North-Sudetic Synclinorium, Sz-M Synclinorium Szczecin-Miechów Synclinorium, WEP West European Platform, WS Western Sudetes, Compilation from Karnkowski (2008Karnkowski ( ), Ż elaźniewicz et al (2011, and Grad et al (1991Grad et al ( , 2003a ▸ 1 3 (WEP), as shown in Fig. 2.…”
Section: Geological and Geophysical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The next profile we discuss is P4 from the POLONAISE'97 experiment. As presented by GRAD et al (2003a), a complicated transition structure across the Trans European Suture Zone (TESZ) from the East European Craton in the North (EEC) to Palaeozoic Platform was derived. The result was a complicated multi layers model [Fig.…”
Section: Application Of the Methodsmentioning
confidence: 99%
“…The MLSZ is traced into north east ern Po land as in di cated by a thick en ing of the crust de fined in the DSS pro files POLONAISSE P4 and P5 (Czuba et al, 2002;Grad et al, 2003). The beltiform lithological fab ric is less dis tinct in this part of the MLSZ be cause on the zone there are su per im posed large cratonic in tru sions such as those of Suwa³ki, Go³dap and Kêtrzyn, form ing a chain in an E-W di rec tion pos si bly con trolled by the large-scale fault struc ture (Wiszniewska et al, 2007).…”
Section: Mid-lithuanian Suture Zonementioning
confidence: 99%